Two Weeks of Low Molecular Weight Heparin for Isolated Symptomatic Distal Vein Thrombosis (TWISTER study). Issue 207 (November 2021) - Merriman, Eileen; Chunilal, Sanjeev; Brighton, Tim; Chen, Vivien; McRae, Simon; Ockelford, Paul; Curnow, Jennifer; Tran, Huy; Chong, Beng; Smith, Mark; Royle, Gordon; Crowther, Helen; et al.
Abstract: Background: Treatment of low-risk patients with isolated symptomatic distal deep vein thrombi (IDDVT) is uncertain. Objective: assess whether two weeks of therapeutic anticoagulation is efficacious/safe for IDDVT. Primary outcome: symptomatic three-month venous thromboembolism (VTE) incidence in the two-week anticoagulation group. Secondary outcomes included post-thrombotic syndrome (PTS) and bleeding. Methods: Prospective multicentre cohort study. Consecutive low-risk IDDVT patients enrolled within 72 h of diagnosis and treated with therapeutic dose enoxaparin or rivaroxaban. At two weeks, patients had repeat complete whole leg compression ultrasound (CUS)/clinical review. If resolution of leg symptoms AND no radiological evidence of thrombus extension, anticoagulation was stopped. If ongoing symptoms and/or radiographic extension within distal veins, anticoagulation was continued for four more weeks. Patients with extension into the popliteal vein on two-week ultrasound were treated off-study. Patients were reviewed at three and six months. Findings/interpretation: 241 eligible patients received ≥2 weeks anticoagulation. 167/241 (69%) were assigned to the 2-week anticoagulation group; 71/241 (30%) to the six-week anticoagulation group; 3/241 patients (1%) had extension into the popliteal vein on two-week CUS. Two patients in the two-week anticoagulation group had symptomatic IDDVT recurrence in ≤3 months; VTE recurrence 2/156; 1.3%(95% CI 0.05–4.85%). 69% of patients had complete resolution of symptoms within two weeks. Six-month PTS rates were 8/184, 4.4%(95% CI 2.1–8.5%). No major bleeding was reported. Our findings suggest it's safe/efficacious to stop therapeutic anticoagulation at two weeks in low-risk IDDVT patients with resolution of symptoms/no extension on ultrasound. This could replace 6–12 weeks of anticoagulation for ambulatory, low-risk IDDVT patients. Trial registration: ClinicalTrials.gov NCT01252420 Highlights: The optimal treatment for isolated distal deep vein deep vein thrombosis (IDDVT) is uncertain. This was a multicentre prospective cohort study enrolling consecutive patients with IDDVT. Two weeks of anticoagulation achieved symptomatic relief in the majority of patients with low-risk IDDVT (69%). Two weeks of anticoagulation was associated with a low risk of recurrent venous thromboembolism (VTE); 1.3%.